Optimization Design of the Transmission System of Small-size Shrub Brush Cutter based on MATLAB - Yang Chunmei; Guo Minghui; Ma Yan; Liu Qianjun; Yang Tie (Jixie chuandong)
In order to change the status of the traditional manual harvesting artificial shrubbery time- consuming,a track- type brush cutter is designed to replace manual labor. Through analyzing the coordinate relationship between the traveling speed and cutting speed of the traditional small self- propelled shrub brush cutter,when the brush cutter in harvesting operations on the bush,the transmission system is the non- continuous transmission function output. So the best coordinate relationship between the traveling speed and cutting speed can’t be got. In order to meet to the requirements of improving the efficiency of small- size self- propelled brush cutter,the optimization design of transmission system of the brush cutter is carried out based on traditional experience design. By determining the objective function of the transmission system,selecting the independent design variables,determining the constraints,the mathematical model of transmission system is established.The analysis and optimization of the design variables,objective function and the boundary conditions are carried out,the complex method optimization program of MATLAB is written,and by using its powerful ability of optimization design to optimize the transmission system of the brush cutter. The optimization results show that,the work efficiency is improved by 20. 59% than the traditional design of small crawler artificial shrub cutter. The design method and the theoretical basis for improving the cutting operation efficiency of the brush cutter are provided.